Biocontrol agents against Penicillium digitatum in 'pera' orange - dos Santos Bonapaz, Rubia; Sousa, Allison John de; Pinto, Suelen Cristina; Kuczer, Marcelo Roberto; Artaban Zórtéa, Emir; Rios Faria, Cacilda Márcia Duarte; Vasconcelos Botelho, Renato (Comunicata Scientiae, 2024)
This work aimed to evaluate the efficiency of biocontrol agents in controlling green mold (Penicillium digitatum) in 'pera' orange fruits. In vitro experiments were carried out with a fungus isolate grown on BDA medium and tested against different concentrations of commercial products based on biocontrol agents: Trichoderma harzianum (0, 5, 10, 15, 20 and 25 mL L -1 ), Bacillus subtilis (0, 2, 4, 6, 8 and 10 mL L -1 ) and B. licheniformis + B. subtilis + T. longibrachiatum (0, 5, 10, 15, 20 and 25 g L -1 ) and the fungicide imazalil as standard (2 mL L -1 ). The experiment analyzed mycelial growth and spore germination. Based on the results, in vivo tests were carried out, evaluating the curative and preventive effect of applying biocontrol agents as inoculating with 10 µL of conidial suspension (108 conidia mL-1). All biochemical agents displayed 100% control over mycelial growth and a linear effect to inhibit the germination of P. digitatum. The in vivo tests highlighted that all agents showed a linear effect, both in the curative and preventive effects, significantly reducing the development of green mold (AUDPC) in 'pera' orange fruits. The experiment concludes that the prophylactic application of 25 mL L -1 of T. harzianum, 10 mL L -1 of B. subtilis, and 25 g L -1 of B. licheniformis + B. subtilis + T. longibrachiatum in orange fruits 'pera' control P. digitatum.